Application of Taqrir Method in Strengthening Santriwati's Al-Qur'an Memory at Hidayatullah Islamic Boarding School Ampenan Sari Garden, Mataram City - Handayani, Diana; Syukri, Syukri (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This article aims to outline the application of the takrir method in enhancing the memorization of the Qur'an and the factors that facilitate or hinder this implementation among female students at the Al-Iman Foundation, Hidayatullah Islamic Boarding School, located in Kebun Sari Ampenan, Mataram City. The research employs a qualitative approach through observation, interviews, and documentation. The findings reveal that the takrir method is applied through four specific techniques, which include group takrir, individual takrir, takrir during prayers, and takrir in the presence of a teacher. These techniques are integrated with tahfidz and tasmi activities: Factors that support and impede the use of the takrir method are identified as follows: Supporting factors include teachers who are strict and consistent despite their limited numbers, parental motivation, a favorable environment for memorization, diligent peers, although some may show laziness and adequate cognitive abilities. Conversely, the hindrances consist of student conditions, such as laziness, fatigue, diminishing enthusiasm, emotional states, issues with memory retention, limited educational resources, particularly regarding teachers/ustazah, and constraints on time. Keywords: Takrir Method, Memorizing the Qur’an, Islamic Boarding School